Curcumin in Turmeric (Curcuma longa L.) for Treatment of Oral Lichen Planus: A Narrative Review - Purwaningrum, Vegananda Wahyu; Elizabeth, Laurencia Dwiamanda; Pratiwi, Chandrasasi Berlian; Nugraha, Ilyas Yakob Nurul; Setiawan, Kresna Erlangga; Maulina, Syafriaz Zulfa; Rahmah, Shafwa Aisha; Shallomitha, Aginta Gracia; Firjani, Putri Nabila; Supandji, Rafaelle Raditya; Salsabila, Alisya Rachel; Islamy, Azzahra Hasnur; Livesey, Gisele Nefertari Love; Masitoh, Hindun Fitria; Fadila, Okta Mulia Nur; Putri, Destiana Hardianti; Cinantya, Aulia Dian; Syahdiar, Aura Zalfa Ghassani; Wati, Sisca Meida; Rahayu, Retno Pudji; Budhy, Theresia Indah; Banerjee, Abhishek (Faculty of Dental Medicine Universitas Airlangga, 2024)
Background: Turmeric (Curcuma longa L.) has long been used as a traditional medicine. The primary active component of turmeric is curcumin. It has potential anti-inflammatory effects and high antioxidant activity. Curcumin contained in turmeric has been reported as an effective treatment for Oral lichen planus (OLP). OLP is a chronic autoimmune, inflammatory disease of the oral mucosa associated with systemic disease. This disease involves the skin and mucous membranes (mucocutaneous) of stratified squamous epithelium. Purpose: This narrative review conducted on Google Scholar, PubMed, Research Gate, and ScienceDirect databases aims to study the effectiveness of curcumin contained in Turmeric (C. longa L.) in OLP treatment. Review(s): OLP is a condition of the oral mucosa that is a chronic autoimmune mucocutaneous disease. As many as 0.5% to 2.2% of cases of OLP occur in the adult population. Systemic and topical corticosteroid drugs are usually used to treat OLP. However, the use of these drugs has many side effects, so it needs searching for a new active substance to treat OLP. Curcumin is a hydrophobic polyphenol extracted from the rhizome of the herb Curcuma longa (turmeric), which has a low molecular weight. The repeated use of steroids can cause side effects that cause atrophy of the mucosa and candidiasis. One natural product that is superior to corticosteroids is curcumin. This is due to curcumin's anti-inflammatory, antioxidant, and chemopreventive properties in several diseases. Conclusion: This review suggests that OLP treatment using curcumin in Turmeric (C. longa L.) is effective because curcumin exhibits antioxidant, anti-inflammatory, antimicrobial, and anticarcinogenic activities, as well as immunomodulatory properties.